Hubungan Antara Usia, Jenis Kelamin dan Jumlah Trombosit dengan Kejadian Demam Berdarah Dengue pada Pasien di Rumah Sakit Umum GMIM Pancaran Kasih Manado - Adelin Sarira; Wulan P. J. Kaunang; Budi T. Ratag (Lembaga Pengembangan Kinerja Dosen, 2025)
Dengue Hemorrhagic Fever (DHF) was an infectious disease caused by the dengue virus transmitted through the bite of the Aedes aegypti mosquito. Factors that influenced the emergence of DHF were divided into three: agent factors (dengue virus), host factors (age, gender, population mobility, education), and environmental factors (physical, biological, and socio-economic environment). DHF diagnosis was confirmed through laboratory criteria, including platelet count and hematocrit increase. This study aimed to determine the relationship between age, gender, and platelet count with the incidence of DHF at GMIM Pancaran Kasih General Hospital Manado. This study aimed to determine the relationship between age, gender, and platelet count with the incidence of dengue hemorrhagic fever among patients at GMIM Pancaran Kasih General Hospital Manado. The research method used in this study was an observational analytic study with a cross-sectional design. Statistical tests were conducted using the chi-square test. It used secondary data from 2024 with a total population of 141 patients. Based on the research results, there was a significant relationship between the incidence of Dengue Hemorrhagic Fever (DHF) and age (p-value 0,025), platelet count (p-value 0.002), and there was no significant relationship between the incidence of DHF and gender (p-value 0.962) at GMIM Pancaran Kasih General Hospital Manado.